2010
DOI: 10.1007/s10620-010-1482-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Anatomic Resection Versus Nonanatomic Resection for Hepatocellular Carcinoma: A Meta-Analysis

Abstract: Anatomic resection is associated with better disease-free survival than nonanatomic resection. Because heterogeneity was detected, caution is needed in interpretation of the results. Better designed, adequately powered studies are required to address this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 34 publications
1
49
1
1
Order By: Relevance
“…To the best of our knowledge, whether hepatectomy for HCC should be performed as an AR or a NAR still remains unclear, because no randomized controlled trials are currently available on this topic. A meta-analysis included nine retrospective studies indicating AR is associated with better disease-free survival than NAR (21). Another meta-regression included 18 observational studies also showed a similar result (22).…”
Section: Hepatic Resectionmentioning
confidence: 93%
“…To the best of our knowledge, whether hepatectomy for HCC should be performed as an AR or a NAR still remains unclear, because no randomized controlled trials are currently available on this topic. A meta-analysis included nine retrospective studies indicating AR is associated with better disease-free survival than NAR (21). Another meta-regression included 18 observational studies also showed a similar result (22).…”
Section: Hepatic Resectionmentioning
confidence: 93%
“…Meanwhile, there is strong evidence that anatomic resection is superior to non-anatomic, i.e., atypical resection for HCC. As evaluated by several meta-analyses, anatomic resection is associated with improved survival rates, and delayed intrahepatic and systemic disease-recurrence with no differences regarding perioperative morbidity or mortality [100][101][102] . Interestingly, one recently published meta-analysis by Tang et al [103] could not demonstrate superiority of anatomic resection, but this seems to be explainable by the different trial selection compared to previous analyses.…”
Section: Anatomic Vs Atypical Resectionmentioning
confidence: 99%
“…Two recent meta-analyses of observational studies have also reported conflicting results (30,31). Importantly, underlying cirrhosis was significantly more common in patients who underwent NAR and who also displayed greater hepatic dysfunction compared to patients who underwent AR.…”
Section: Anatomical Vs Non-anatomical Resectionmentioning
confidence: 99%